Improved geopolymerization of bottom ash by incorporating fly ash and using waste gypsum as additive - Kornkanok Boonserm (2018)
This research studied the improvement of the geopolymerization of bottom ash (BA) by incorporating fly ash (FA) and using flue gas desulfurization gypsum (FGDG) as additive. The BA:FA ratios of 100:0, 75:25, 50:50, 25:75, and 0:100 were used as the blended source materials. The source materials were then replaced with 0%, 5%, 10%, and 15% of FGDG. NaOH, sodium silicate and temperature curing were used to activate the geopolymer. Test results indicated that the increase in FA content in the BA-FA blends improved the strengths of geopolymer mortars owing to the high glassy phase content and high reactivity of FA compared to those of BA. The use of up to 10% of FGDG as additive also significantly increased the strengths of geopolymer. In this case, the compressive strength enhancement was due to the increase in the Al3+leached from BA in the presence of SO42- and the formation of additional calcium silicate hydrate. © 2012 Elsevier Ltd. All rights reserved.